Detection and Classification of Leukocytes in Bone Marrow Images Using ARTMAP Neural Network - Arthi, R (International Journal of Computer Sciences and Engineering, 2020)
This paper provides a model-based tracking framework for classifying the leukocytes in bone marrow images. Detecting and classifying the leukocytes is an established problem in image analysis and machine learning. This system aims to automate the process of detecting, differentiating and classifying the leukocytes. The process of automatic recognition requires the extraction of individual cells, generation of features and finally the classification using ARTMAP Neural Network classifier. For many illnesses, classifying the blood cell is used as a diagnostic technique in the detection of many illnesses, particularly leukemia. This system uses two phase methodology. The first phase includes the preprocessing methods of the bone marrow images. The second phase, classifies these features using pattern recognition techniques into a number of given families. This system uses the ARTMAP Neural Network classifiers for characterizing different types of cells.